Professional Search in the Modern World COST Action IC1002 on Multilingual and Multifaceted Interactive Information Access - Paltoglou, Georgios; Loizides, Fernando; Hansen, Preben; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This State-of-the-Art Survey constitutes the Final Publication of the COST Action IC1002 on Multilingual and Multifaceted Interactive Information Access, MUMIA. It contains outstanding research, recent developments and new directions in all related aspects of multifaceted and interactive information access with a focus on professional and enterprise search. The contributions are grouped in the following three parts: frameworks, models and theory; tools, applications and practice; and patent search. The Intellectual Property (IP) domain is used through the book as a primary case study. The book aims to bring together material which has been published in a fragmentary way in journals and conference papers into a coherent whole but also present novel, unpublished work where appropriate.
Introduction to Professional Search -- Frameworks, Models and Theory -- A Use Case Framework for Information Access Evaluation -- Users$1 (BInformation Search Behavior in a Professional Search Environment: A Methodological Approach -- Information Retrieval for R&D Support -- 21st Century Search and Recommendation: Exploiting Personalisation and Social Media -- Domain Specific Search -- Tools, Applications and Practice -- ezDL: An Interactive IR Framework, Search Tool, and Evaluation System -- Clinical Text Retrieval - An Overview of Basic Building Blocks and Applications:- Exploratory Professional Search through Semantic Post-Analysis of Search Results:- Opinion Retrieval: Searching for Opinions in Social Media:- Patent Search:- A Survey of Automated Hierarchical Classification of Patents:- Enhancing Patent Search with Content-Based Image Retrieval.s
Keywords: Computer science; Information storage and retrieval; Multimedia information systems; User interfaces (Computer systems).; Computer Science; Information Storage and Retrieval; Multimedia Information Systems; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Electronic books